2008
DOI: 10.2478/s11756-008-0137-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, palynology and nutlet micromorphology of Turkish endemic Teucrium sandrasicum (Lamiaceae)

Abstract: In this study, the anatomical features of the leaf and stem, besides the pollen and nutlet characteristics of Teucrium sandrasicum are investigated. T. sandrasicum, belonging to sect. Teucrium, is an endemic perennial herb growing on serpentine around Mugla province. The anatomical studies on T. sandrasicum revealed that the stem shares the general characteristics of the Labiatae family. The leaves clearly exhibit xeromorphy due to features such as the distribution of stomata on the lower surface (hipostomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 5 publications
7
23
0
Order By: Relevance
“…In cross-section, the stem is quadrangular, collenchyma tissue covers a large area at the corner and one-two layers betweeen the corners. These features are previously reported in some other investigated members by several authors (Metcalfe and Chalk 1972, Bosabalitis and Kokkini 1997, Gönüz and Özörgücü 1999, Dinç et al 2008. On the other hand, the cortex size and collenchyma thickenes in the corners, trachea size and pith cell size O. vulgare ssp.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In cross-section, the stem is quadrangular, collenchyma tissue covers a large area at the corner and one-two layers betweeen the corners. These features are previously reported in some other investigated members by several authors (Metcalfe and Chalk 1972, Bosabalitis and Kokkini 1997, Gönüz and Özörgücü 1999, Dinç et al 2008. On the other hand, the cortex size and collenchyma thickenes in the corners, trachea size and pith cell size O. vulgare ssp.…”
Section: Resultssupporting
confidence: 63%
“…It is reported that high density of trichomes and thick palisade tissue of mesophyll could be interpreted as xerophytic characters. These features were reported in T. sandrasicum (Dinç et al 2008), T. montanum and T. polium (Dinç et al 2011). The upper epidermal cells are distinctly larger than the lower ones in T. hircanum, while it is almost equal to the lower one in O. rotundifolium.…”
Section: Resultsmentioning
confidence: 51%
“…Metcalfe & Chalk (1950) pointed out that the stems of the family Lamiaceae species are rectangular and the collenchymatic tissue covers broad area at the corners, and a developed scleranchymatic tissue surrounds the vascular tissue. The anatomical studies on some of the genus Teucrium species showed that they had the same anatomical characteristics as well (Dinç et al 2008a(Dinç et al ,b, 2009. In contradistinction to previously…”
Section: Discussionmentioning
confidence: 99%
“…The more restricted occurrence of the spherocrystals enhances its diagnostic value (Metcalfe & Chalk 1983). Spherocrystals are present in leaf epidermal cells of some species from section Teucrium and section Scordium (Dinç et al 2008a(Dinç et al ,b, 2009). The presently studied species from section Polium lack spherocrystals.…”
mentioning
confidence: 99%
See 1 more Smart Citation